The factors affecting the demand of medical insurance among employees / Muhammad Fakhrur Razi Saedi - Saedi, Muhammad Fakhrur Razi (Faculty of Business and Management, Universiti Teknologi MARA, 2010)
Medical Insurance is very important in order to cover the cost of private medical treatment, which can be very expensive, especially with hospitalization and surgery. Medical Insurance also ensures that insured won’t have to worry about the cost of seeking treatment during emergencies. This research is conducted in order to find out the factors that affecting demand of Medical Insurance among employees. This research basically focuses on the employees area Kampung Attap at Kuala Lumpur. The researcher tried to clarify what factors that can affecting demand of Medical Insurance. The researcher is being narrowed to 50 and randomly chosen respondents as the data sampling in order to get information regarding those factors. By this research, there are several parties will gain benefits such as Researcher, Insurance Companies, Insurance Intermediaries and Insurance Industry. This information will used by them to increase the premium contribution of Medical Insurance.